Development of Malay word pronunciation application using vowel recognition - Mohd Yusof, Shahrul Azmi (SERSC, 2016)
In Malaysia, many researchers focus on developing speaker independent systems for training or articulation therapy or to assist language learners to learn about Malay Language or Bahasa Malaysia.Accuracy, noise robustness and processing time are concerns when developing speech therapy systems.In this study, a Malay word pronunciation test application was developed using the first 3 format and fundamental frequencies in an effort to improve pronunciation in Malay.This application was developed using Matlab and uses a vowel recognition algorithm classified using MLP classification technique.The application was developed and tested on UUM undergraduate students.For vowel classification, when fundamental frequency was added, 3-format feature vowel classification rate increased by 1.55% for male gender and 1.48% for female. When combined both genders, a more significant improvement of 1.71% was seen.The developed pronunciation application test results showed that the pronunciation application can assist in testing and improving their Malay word pronunciation. It was also observed that, vowel /i/, /e/, /o/ and /u/ are often mispronounced due to pronunciation habits.